Grain surface features and clay mineralogy of the quaternary sediments from Western Deccan Trap Region, India, and their palaeoclimatic significance - Joshi, Veena (Acta Geographica Debrecina Landscape & Environment series, 2011)
Quartz sand grains obtained from a deeply gullied topography along the banks of two tributaries of River Pravara in Maharashtra (India) have been examined with a scanning electron microscope (SEM). Quartz grains have been selected after a heavy mineral separation and micro-photographs of each grain were taken at various angles and magnifications. The sediments reveal features resulting from mechanical grinding as well as from chemical alteration. Conchoidal fractures, cleavage planes, grooves, v-shaped indentations etc. are the mechanical features documented on the grains whereas solution pits of varying sizes and intensity, precipitation surfaces, oriented v-pits, solution crevasses and etching are the features of chemical origin. Several evidences indicate that the samples have undergone digenetic changes. Few grains show the features of intense chemical breakdown. The overall assemblages of the grain surface features suggest that the samples have been subjected to subaqueous transport for a considerable period of time. The minor chemical features such as solution pits or semi circular arcuate steps found in abundance on these grains are due to the dissolution of the sediments in a low energy fluviatile environment. For clay mineralogy, fractions between <2 and <0.2 mm were separated out from the sediments. The clay fractions were then subjected to examination by X-ray diffraction (XRD) of oriented K/Ca saturated samples using a Philips Diffractometer and Nifiltered Cu Ka radiation with the scanning speed of 1 0 2Ө min -1. The main clay minerals for all the samples are identical and show the presence of hydroxy-interlayered smectites with minor quantities of mica, kaolinite, smectites, quartz and feldspar. The first weathering product of the Deccan Basalt (DB) is the dioctahedral smectite. Since the present semi aridic climatic condition of the study area can not transform a smectite to HIS and either smectite to kaolin, it is quite likely that both the HIS and Sm/K are generated in the tropical humid climate of the Western Ghats and then carried through the exiting river system like Godavari, Adula and Mahalungi. Therefore it is evident that the clay minerals present in these sediments represent another climatic history more humid than the one prevailing at present.